2013
DOI: 10.1093/jxb/ert273
|View full text |Cite
|
Sign up to set email alerts
|

Making open data work for plant scientists

Abstract: Despite the clear demand for open data sharing, its implementation within plant science is still limited. This is, at least in part, because open data-sharing raises several unanswered questions and challenges to current research practices. In this commentary, some of the challenges encountered by plant researchers at the bench when generating, interpreting, and attempting to disseminate their data have been highlighted. The difficulties involved in sharing sequencing, transcriptomics, proteomics, and metabolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…Although multiple studies have found some evidence of correlation between shared data and higher citation counts, it either did not occur to the researchers in this study that this was a possibility, or this is not a major motivating factor for them (Drachen et al 2016;Piwowar & Vision 2013;Thelwall & Kousha 2017). Another benefit not cited by the agricultural researchers in the Ithaka S+R study is the ability to make "negative" or otherwise unpublished data available, although it has been noted by other scientists (Keil 2014;Leonelli et al 2013). For librarians, both of these advantages could be explored with agricultural researchers to determine whether they are motivators.…”
Section: Motivation and Benefitsmentioning
confidence: 67%
“…Although multiple studies have found some evidence of correlation between shared data and higher citation counts, it either did not occur to the researchers in this study that this was a possibility, or this is not a major motivating factor for them (Drachen et al 2016;Piwowar & Vision 2013;Thelwall & Kousha 2017). Another benefit not cited by the agricultural researchers in the Ithaka S+R study is the ability to make "negative" or otherwise unpublished data available, although it has been noted by other scientists (Keil 2014;Leonelli et al 2013). For librarians, both of these advantages could be explored with agricultural researchers to determine whether they are motivators.…”
Section: Motivation and Benefitsmentioning
confidence: 67%
“…If the data are accessible and reusable, researchers can examine and generate new knowledge 1 . Today, the rapid advances in computing capabilities provide useful tools in manipulating and exploring massive data sets 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Within the traditional system of publishing research data, only a small fraction of the data is available to the public, and in addition, the selection of these data depends on the value that the authors give to the published article [2][3][4].…”
Section: Introductionmentioning
confidence: 99%